Severity and Complications of Injury, Levels of Activity and Participation in Individuals with Spinal Cord Injury - Olumide Dada; Adelana Ogunleye (The Center for Disability Studies and Services Brawijaya University, 2022)
The cross-sectional survey investigated the prevalence of complications of SCI, levels of activity and participation and the associations among them. The ASIA impairment scale, Impact on Participation and Autonomy Questionnaire, Barthel’s index and Numeric Pain Rating Scale were used to assess participation, activity and pain respectively. Pain was the most prevalent complication among the 25 participants. 68% of them had high level of activity and 72% had moderate level of participation and autonomy. There was a significant association between level of activity and presence of pressure ulcer and bladder dysfunction but there was no significant association between pain and level of activity. There was significant association between level of participation and presence of pressure ulcer, bladder dysfunction and pain. There was no significant association between level of activity and participation. The level of activity and participation among individuals with SCI appeared to be influenced by presence of complications.